promotion image of download ymail app
Promoted

Solve this?

Attachment image

2 Answers

Relevance
  • Favorite Answer

    f(-2.8) = 4

    f(1.2) = 0

    f(pi) = -2

    f(-1) = 2

    f(2) = -1

    f(-pi) = 5

    I can forgive crappy notation from a student, but this problem is setup by a moron. Is that a division between f(-1) and f(2)? If so, then do they want it to be f(-1) / (f(2) * f(-pi)) or do they want f(-1) * f(-pi) / f(2)? It matters.

    sqrt(4 + 0) - (-2)^2 + 2 / ((-1) * 5) =>

    sqrt(4) - 4 + 2 / (-5) =>

    2 - 4 - 2/5 =>

    -2 - 2/5 =>

    -12/5

    or

    sqrt(4 + 0) - (-2)^2 + 2 * 5 / (-1) =>

    2 - 4 + 10/(-1) =>

    2 - 4 - 10 =>

    2 - 14 =>

    -12

    One of those is right. Bring up the crappy notation with your teacher or professor.

    • Commenter avatarLogin to reply the answers
  • 10 months ago

    f(-2.8) = 4

    f(1.2) = 0

    f(pi) = -2

    f(-1) = 2

    f(2) = -1

    f(-pi) = 5

    Or you can use 1 - floor(x)

    • Commenter avatarLogin to reply the answers
Still have questions? Get your answers by asking now.